2017
DOI: 10.1016/j.carbpol.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graft copolymers based on hyaluronan and poly(3-hydroxyalkanoates)

Abstract: This work reports the synthesis and characterisation of new amphiphilic hyaluronan (HA) grafted with poly(3-hydroxyalkanoates) (PHAs) conjugates. Hydrolytic depolymerisation of PHAs was used for the synthesis of defined oligo(3-hydroxyalkanoates)-containing carboxylic terminal moieties. A kinetic study of the depolymerisation was followed to prepare oligomers of required molecular weight. PHAs were coupled with hydroxyl groups of HA mediated by N, N'-carbonyldiimidazole (CDI) or HSTU Tetramethyl-O-(N-succinimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…[29] An even wider spectra of PHA polymers can be synthesized via grafting, for instance with hyaluronan, or co-polymerization of the microbial polymers. [30] Chemical modifications are favored for low molecular weight PHAs, because they are soluble in organic solvents such as tetrahydrofuran (THF) and dimethylsulfoxide (DMSO). [28b] Recently a review of PHA based nanovesicles was published, in which the formation of both micelles and vesicles were described based on poly(3hydroxyoctanoate-co-3-hydroxyundecenoate) (PHOU) amphiphilic graft copolymers.…”
Section: Polyhydroxyalkanoatesmentioning
confidence: 99%
“…[29] An even wider spectra of PHA polymers can be synthesized via grafting, for instance with hyaluronan, or co-polymerization of the microbial polymers. [30] Chemical modifications are favored for low molecular weight PHAs, because they are soluble in organic solvents such as tetrahydrofuran (THF) and dimethylsulfoxide (DMSO). [28b] Recently a review of PHA based nanovesicles was published, in which the formation of both micelles and vesicles were described based on poly(3hydroxyoctanoate-co-3-hydroxyundecenoate) (PHOU) amphiphilic graft copolymers.…”
Section: Polyhydroxyalkanoatesmentioning
confidence: 99%
“…Studies by other researchers show that acetic acid tends to degrade P3HB at high temperatures (110 °C), which is consistent with the results obtained and explains the sharp reduction in molecular weight obtained for the polymer purified using the solvent‐casting technique which occurs at 120 °C. Additionally, it is shown that the loss of molecular weight behaves exponentially with respect to time, indicating that one way to reduce the loss of molecular weight is by optimizing the process times, to reduce the contact of P3HB with the solvent as much as possible . However, the molecular weight of the sample obtained using methanol precipitation is not very different from that of the chloroform sample, indicating that this new methodology allows one to obtain a polymer with characteristics similar to those of polymer obtained using the conventional method.…”
Section: Resultsmentioning
confidence: 93%
“…synthesized a graft copolymer based on PHA and HA. They obtained the carboxy‐terminated oligo(3‐hydroxyalkanoate) by hydrolysis‐depolymerization of PHA, and then coupled with the hydroxyl group of HA under the guidance of N , N ′carbonyldiimidazole to obtain up to 14% PHA–HA copolymer of grafting degree . This new type of copolymer is quite important for developing some new applications.…”
Section: Synthesis Of Polyhydroxyalkanoatesmentioning
confidence: 99%